HUACA NARANJAL: A CENTER OF PRODUCTION OF POTTERY YCHSMA STYLE IN THE CHILLON VALLEY - Maquera Sánchez, Erik E. (2008)
Recent excavations at Huaca Naranjal have registered the recurrence of large pottery sherd contexts, which have been recognized as a waste of pottery production. The analysis of the contexts indicates that the ceramics produced is part of restricted types of Ychsma style result of a pattern of specialize production, that enables the discussion of the socio-economic organization of the population. The recognition of an Ychsma style production pottery center in the lower valley of Chillon poses the problem on its political identification, considering its proximity to the ethnohistoric defined Colli.